Pesticide poisoning notified by the Department of Health Surveillance of Sousa-PB - Queiroz, Paulo Roberto; Oliveira, Andréa Brandão Mendes de; Coelho, Luiz Fernando Oliveira (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2014)
Agrotoxic it’s a national designation given to the chemical substance or mixture of substances used to control or destroy a variety of undesirable life organisms. These substances are potentially toxic to humans, because they are dangerous for who often use them without any protection and quite often, as is the case for most farmers. This research aimed to describe the profile epidemiology of intoxications by agro-toxics and to assess the quantity of cases notified by the Department of Health Surveillance from Sousa / PB. We realizeda descriptive, exploratory research with a retrospective analysis of epidemiological records of Toxicological Occurrence and individual investigation files about agro-toxic poisoning between January 2008 and June 2013. For the data processing was used the software Excel 2003, and the analysis by simple descriptive statistics were used. 13 cases were analyzed, noting that poisonings were more prevalent in males - 84.61%, in the age group of 30 to 39 years - 46.15% and 53.84 % occurred in the urban area, with 61.53 % of intoxicated designating themselves as farmers. The most prevalent conditions were suicide attempts, with 69.23 % of cases, followed by occupational exposure, with 23.07% of cases. The Insecticides stood out among the chemical class of more events-38.46 % of cases, the organophosphates (HALs) among the chemical groups it has been found the highest incidence - 46.15 % of cases. The predominance of agro-toxic poisoning, although it was lower when compared to other researches was considered high. We also emphasize the importance of epidemiological researches and continuing education policies aimed at the prevention of this disease.